Encapsulation and controlled release of an antimalarial drug using surface functionalized mesoporous silica nanocarriers. Issue 25 (21st June 2021) - Hirayama, Haruka; Amolegbe, Saliu Alao; Islam, Md. Saidul; Rahman, Mohammad Atiqur; Goto, Nonoka; Sekine, Yoshihiro; Hayami, Shinya
Abstract : The pH and thermal optimization effects on the encapsulation and release of antimalarial drug quinine using three nanocarriers, including MCM-41, and its 3-aminopropyl silane and 3-phenylpropyl silane functionalized derivatives, were investigated. Abstract : Herein, we report the encapsulation and release of antimalarial drug quinine (QN) using three nanocarriers, including MCM-41 (1 ), and its 3-aminopropyl silane (aMCM-41 (2 )) and 3-phenylpropyl silane (pMCM-41 (3 )) surface functionalized derivatives. The pH and thermal optimization effects on QN adsorption and release from 1, 2 and 3 were investigated.